Imaging Review of Alpine Ski Injuries - Flores, Dyan V.; Murray, Timothy É.; Bohyn, Cedric; Mohr, Bruce; Cresswell, Mark (Seminars in Musculoskeletal Radiology, 2022)
Skiing is a continuously evolving winter sport, responsible for a considerable number of musculoskeletal injuries. Specific injury patterns and mechanisms in the upper and lower extremities, head, and spine are influenced by skier expertise and skill, position during injury, and environmental conditions. Predilection for certain joints and injury patterns have changed over time, largely due to technological advancements in equipment, increased awareness campaigns, and preventive protocols. Knowledge and understanding of these trends and developments can aid the radiologist to reach a timely and accurate diagnosis, thereby guiding clinical management and potentially reducing the overall incidence of debilitation and death.
Keywords: skiing; sports injuries; imaging; injury mechanism